Integrated resource management in Canada: Enhancing the federal role in water management. - Will, Edward John. (University of Ottawa (Canada), 1993)
Water management by government is becoming a more difficult and complex task, as increased natural resource development and other industrial and municipal pressures impact cumulatively on the very resources that centrally support each of these needs. Coming to grips with this cumulative attack on the ecosystem has frustrated the public, as well as the leaders of both public and private sectors, as resource development proposals seemingly get hung up in public reviews in which the proponent, the public and the scientific community are not able to agree on what form of development is both desirable, from a socio-economic standpoint, and reasonable, given environmental limits. The capacity of current institutional arrangements for resource management is not providing the opportunity for the kind of integrated decision-making needed. Consequently, such conflicts are being settled in the courts, rather than within the institutional arrangements established for the purposes of resource management. Previous research has indicated that current institutional arrangements for resource management are designed for a past era when water issues were dealt with on a sectoral basis in relation to emerging crises. This had made it difficult for any integrated effort to be made by interested parties involved when focused in a particular geographical area. Reinforcing this difficulty is the constitutional division of responsibility for resource management between federal and provincial governments. As a microcosm of this general circumstance, the Alberta-Pacific (AL-PAC) pulp mill proposal assessment and review is used as a case study and entry point for assessing current weaknesses in institutional arrangements for resource management. Through the development and application of an evaluation framework, contextual factors and weaknesses in legislation, policies, processes and mechanisms that had a bearing on the case were identified and described. These weaknesses served as leverage points for prescribing recommended actions to achieve integration in resource management and for gaining an enhanced federal role in water management. Data collected were derived from three main sources: correspondence/newsclippings; official documentation, such as legislation, policies, reports, etc.; and interviews conducted with persons representing key stakeholder groups. The latter source provided perspectives on both weaknesses and needed changes. The study concluded that current barriers to integration are found in inadequate linkages among institutional arrangements, within each stage of the resource management process (e.g., lack of cohesiveness), and similarly within individual components of the institutional arrangements. By way of example, in the former instance, institutional arrangements are not designed to require the completion of regional land-use planning in a given geographical area prior to the consideration of a major project. In the latter instance, individual statutes and policies are vague and, at best, only implicit in directing attention to any interests other than respective sectoral interests. The implications of the study are considerable. If ecosystem health, and thus water management, are to be treated seriously by governments, a political commitment to embodying a capability for integration in resource management is essential. Requirements for integration should be built into all resource-related institutional arrangements within the management process. While all governments are responsible for bringing this about, the federal government should provide the leadership for developing, with the provinces, new approaches for achieving integrated resource management. A number of such approaches are recommended.
Keywords: Geography.